A 15-min non-competitive homogeneous assay for microcystin and nodularin based on time-resolved Förster resonance energy transfer (TR-FRET) - Akter Sultana; Lamminmäki Urpo (Springer, 2022)
Simple and rapid methods are required for screening and analysis of water samples to detect cyanobacterial cyclic peptide hepatotoxins: microcystin/nodularin. Previously, we reported a highly sensitive non-competitive heterogeneous assay for microcystin/nodularin utilizing a generic anti-immunocomplex (anti-IC) single-chain fragment of antibody variable domains (scFv) isolated from a synthetic antibody library together with a generic adda ((2S,3S,4E,6E,8S,9S)-3-amino-9-methoxy-2,6,8-trimethyl-10-phenyldeca-4,6-dienoic acid)-specific monoclonal antibody (Mab) recognizing the common adda part of the microcystin/nodularin. Using the same antibody pair, here we report a homogeneous non-competitive assay for microcystin/nodularin based on TR-FRET (time-resolved Förster resonance energy transfer) measurement. The anti-IC scFv labeled with Alexa Fluor 680 and the Mab labeled with europium enabled the FRET process to occur in the presence of microcystin/nodularin. The TR-FRET signal is proportional to the toxin concentration in the sample. The rapid (15 min) homogeneous assay without requiring any washing step detected all the tested nine toxin variants (microcystin-LR, -dmLR, -RR, -dmRR, -YR, -LY, -LF -LW, and nodularin-R). Very good signal to blank ratio (~13) was achieved using microcystin-LR and the sample detection limit (blank+3SD of blank) for microcystin-LR was ~0.3 μg/L (~0.08 μg/L in 80-μL reaction well). The practical application of the TR-FRET assay was demonstrated with water samples spiked with microcystin-LR as well as with environmental water. The average recoveries of microcystin-LR from spiked water ranged from 65 to 123%. Good correlation (r2 = 0.73 to 0.99) with other methods (liquid chromatography-mass spectrometry and previously reported heterogeneous assay) was found when environmental samples were analyzed. The developed wash-free assay has the potential to play as a quick screening tool to detect microcystin/nodularin from water below the World Health Organization’s guideline limit (1 μg/L of microcystin-LR).